2009
DOI: 10.1089/ten.tea.2009.0024
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Embryonic Stem Cell Differentiation Promoted by Avian Chorioallantoic Membranes

Abstract: Avian chorioallantoic membrane (CAM) has been used as a model to explore angiogenesis and to study the microvasculature of transplanted tissues. Because CAM provides a vascular bed, cells can be implanted, and their development can be monitored and modified. We used the CAM model to study the differentiation process of embryoid bodies (EBs) derived from mouse embryonic stem cells (ESCs) influenced by the CAM vascular bed. After EBs were incubated in CAM for 5 days, they underwent further differentiation and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Our results support this hypothesis since scarce blood circulation was observed in the blood vessels yet the differentiation enhancement took place. In addition, we reported enhancement of differentiation using mouse EBs implanted in surrogate vasculature from quail embryos [7]. These findings also support the idea of EC-derived factors as mediators of the differentiation process.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Our results support this hypothesis since scarce blood circulation was observed in the blood vessels yet the differentiation enhancement took place. In addition, we reported enhancement of differentiation using mouse EBs implanted in surrogate vasculature from quail embryos [7]. These findings also support the idea of EC-derived factors as mediators of the differentiation process.…”
supporting
confidence: 84%
“…With the emergence of embryonic stem cells (ESCs), studies to investigate the role of ECs in organogenesis can now be performed in vitro. We previously described an approach to investigate the inductive effects of ECs in cell differentiation by implanting embryoid bodies (EBs) into surrogate vascular beds, such as quail chorioallantoic membranes [7]. Recently, we also reported the enhancement of pancreatic progenitors and insulin-producing cells in EBs cocultured with human microvascular endothelial cells (HMECs) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The blood capillaries were found to grow radially towards the hDPSC-containing matrigel droplets. These findings suggest that the secretion of angiogenic molecules is responsible for the hDPSC-induced angiogenesis in the CAM, as the applied incubation period of 72 hours is considered to be too short to induce EC transdifferentiation of the transplanted cells [45], [55], [56]. Undifferentiated and endothelial-differentiated placental MSC also have angiogenic activities in this in vivo -like animal model [55].…”
Section: Discussionmentioning
confidence: 90%
“…We found that some cells expressed cardiotin, myosin heavy chain, collagen Ⅳ, CD34, CD31, and neurofilament. Although some epithelial cells appeared, no cells derived from endoderm were identified [90] . Then, studies using co-cultures between human microvascular ECs (HMECs) and mouse EBs were performed [52,53,91] .…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 99%
“…As a first approach to investigate the role of endothelium in b-cell differentiation, we studied the role of in vivo surrogate vasculature in mouse embryoid body (EB) differentiation using quail chorioallantoic membranes (CAM) [90] . We found that some cells expressed cardiotin, myosin heavy chain, collagen Ⅳ, CD34, CD31, and neurofilament.…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 99%